Architecture of the motor and premotor cortex of the capuchin monkey - Magalhães-Junior, Erli G.; Mayer, Andrei; Nascimento-Silva, Márcio L.; Bonfim, Vânio; Lima, Bruss; Gattass, Ricardo; Soares, Juliana G. M. (Frontiers in Mammal Science, 2023)
Introduction Over the last 65 million years, primates have evolved hind- and forelimbs capable of skilled grasping (e.g., tree branches) and manipulation of tools and other objects. The New World capuchin monkey and the Old World macaque monkey stand out among other primates for their manual dexterity. The capuchin monkey is distributed throughout the Amazon and the Atlantic Forests and is the only New World monkey to have evolved an opposable thumb and to have developed the capability of using tools in the wild. Methods The present work analyzes the cyto-, myelo- and immunoarchitecture of the motor and premotor areas of the capuchin monkey using Nissl, Gallyas and SMI-32 immunolabeling techniques. Results These different staining techniques allowed for the parcellation of Brodmann area 4 into the ventral (F1v), medial (F1m) and dorsal (F1d) areas. Additionally, lateral area 6 was subdivided into the dorsal (F2 and F7) and ventral (F4 and F5) areas. Area F5 was subsequently subdivided into the convexity (F5c), anterior (F5a) and posterior (F5p) areas. Medial area 6 was subdivided into F3 and F6 areas. Discussion These motor and premotor areas of the capuchin monkey are similar to those of macaque and humans, and different from those of other New World monkeys. We argue that this is due to differences in manual dexterity across New World monkeys: capuchin monkeys have evolved different types of precision grips, while most of the other New World monkeys exclusively perform whole-hand grips during object manipulation.